2020
DOI: 10.57178/atestasi.v3i2.255
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affect Budget Absorption In Government Institutions of South Sulawesi

Abstract: The purpose of this study was to analyze and study the effect of financial regulations, budget absorption, apparatus competence, bureaucratic environment, and organizational commitment to budget absorption by the South Sulawesi Provincial Government to be able to provide input for the policies of the South Sulawesi Provincial Government in maximizing budget absorption. This study's population was all employees of the South Sulawesi Provincial Government. They determined the sample using the technique Judgment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
2
8
0
1
Order By: Relevance
“…The proposed budget is more significant than required without considering the ease of implementation and real needs in the field. However, in contrast to (Ramdhani & Anisa, 2017;Putri et al, 2018;Ramadhani & Setiawan, 2019;Lannai & Amin, 2020) finding that budget planning has a positive and significant effect on budget absorption. Administrative records are vital so that they can be used as evidence of recording, decision making, and reporting to influence budget absorption properly.…”
Section: Discussionmentioning
confidence: 72%
“…The proposed budget is more significant than required without considering the ease of implementation and real needs in the field. However, in contrast to (Ramdhani & Anisa, 2017;Putri et al, 2018;Ramadhani & Setiawan, 2019;Lannai & Amin, 2020) finding that budget planning has a positive and significant effect on budget absorption. Administrative records are vital so that they can be used as evidence of recording, decision making, and reporting to influence budget absorption properly.…”
Section: Discussionmentioning
confidence: 72%
“…The results of research by Koriatmaja et al, (2020), Putri et al, (2021), Lannai & Asbi (2020), Sari et al, (2019) and Oktaria et al, (2020) found that budget planning has a positive effect on budget absorption. In contrast to the research results of Sirin et al, (2020) which found that budget planning has a negative effect on budget absorption.…”
Section: Figure 1 Unnes 2017-2021 Budget Realizationmentioning
confidence: 98%
“…In the research conducted by (Lannai & Amin, 2020;Pratiwi, N. R. et al, 2023) states regulation is positively and significantly related to budget absorption. It also states that regulation has a significant positive effect on budget absorption (Ramadhani & Setiawan, 2019;Ramdhani & Anisa, 2017).…”
Section: Introductionmentioning
confidence: 99%